mTOR-Dependent and Independent Survival Signaling by PI3K in B Lymphocytes - Kaileh, Mary; Vazquez, Estefania; MacFarlane, Alexander W.; Campbell, Kerry; Kurosaki, Tomohiro; Siebenlist, Ulrich; Sen, Ranjan (PloS one, 2016)
Peripheral B lymphocyte survival requires the B cell receptor (BCR) and B cell activating factor (BAFF) binding to its receptor (BAFF-R). Deletion of the BCR, or its signal transducing chaperone Igβ, leads to rapid loss of mature B cells, indicating that signals initiated at the BCR are crucial for B cell survival. BAFF or BAFF-R deficiency also significantly reduces the numbers of mature B cells despite normal BCR expression. Together, these observations indicate that continued BCR and BAFF-R signaling are essential for the survival of mature resting B cells in the periphery. Here we demonstrate that tonic BCR signals up-regulate p100 (Nfkb2) as well as Mcl-1 protein expression at a post-transcriptional level via a PI3K-dependent pathway. p100 expression is mTOR-independent, whereas Mcl-1 expression is mTOR-dependent. BAFF treatment further elevated Mcl-1 levels by an mTOR-independent pathway, while consuming p100. Accordingly, Mcl-1 induction by BAFF is abrogated in Nfkb2-/- B cells. We propose that the cumulative effects of the BCR and BAFF-R signaling pathways increase Mcl-1 levels beyond the threshold required for B cell survival.